SEMANTIC FEATURES OF PHYTOOIKONIMICA VAST IN POLISH AND UKRAINIAN LANGUAGES - Lazarovich, O. M.; Yaremyn, O. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article raises the actual problems of classification of toponyms, considers the basic aspects of genetically-semantic division of V. Tashicky, includes the comparative analysis of semantic groups of phytooikonim of the Polish and Ukrainian languages.